SOSIALISASI PENGISIAN SISTER BAGI DOSEN PESERTA SERTFIKASI DOSEN TAHUN 2020 - Roki Hardianto; Wirdahchoiriah Wirdahchoiriah; Fana Wiza (Jurnal Pengabdian Masyarakat Multidisiplin, 2020)
This activity is to provide assistance to the group of Lancang Kuning University lecturers, especially to the lecturers participating in the Phase I lecturer certification in 2020. The service team will explain the techniques and methods of collection starting with explaining the functions of the Sister application (www.sister.unilak.ac.id ) for lecturers both lecturer certification participants and certified lecturers. Certification participants must enter their personal data, educational history, functional position history, education implementation history, research history, service history and other supporting data. All participants explained the rules in the process of inputting data, especially the maximum size of data that can be input up to a quick trick in order to be able to input data themselves on the application. Of the 10 faculties at Lancang Kuning University, 72 lecturers can continue at stage D3 to stage D4. Whereas at stage D5 only 51 lecturers were able to proceed because of the selection process for the assessment of the system. The dedication team made WAG in guiding the data system input process in the framework of the certification process. This is done so that they can monitor and assist if there are obstacles in the certification process.